Star Wars origami : 36 amazing paper-folding projects from a galaxy far, far away-- - Alexander, Chris, 1963- (New York : Workman Publishing, 2012)
Presents instructions for creating over thirty origami projects resembling key characters, ships, and objects in the "Star Wars" film franchise, and includes quizzes and trivia on the six films.
Includes index.
Keywords: Star Wars films -- Miscellanea; Origami